Synthesis and characterization of low density Bi(Pb)-2223 high temperature superconductor doped with europium and ytterbium / Nor Azura Che Mahmud - Che Mahmud, Nor Azura (2016)
The conventional solid state reaction method was conducted in synthesizing low density Bi1.6Pb0.4Ca2Sr2Cu3Oy High Temperature Superconductor doped with Europium and Ytterbium. The morphology and structural identification, elemental composition, critical temperature and critical current were determined by Field Emission Scanning Electron Microscopy (FESEM), X-Ray Diffraction (XRD), Energy Dispersive Spectrometry (EDS) and four point probes respectively. The optimum level of low density superconductor obtained within the sample with ratio of polycrystalline sucrose to Bi(Pb)-2223 powder was at 0.050:1.950, where the highest Jc obtained was 6.053 A/cm2 at 77 K. The effect of rare earth elements, RE (Yb and Eu) substitutional doping in the optimum level of low-density (Bi1.6Pb0.4Sr2 RExCa2-xCu3Oy), high-temperature superconductor have shown that for all series of doping concentration, the 7c and Jc gradually decreased as x is increased. XRD analyses at varying concentration of doping level confirmed that at starting composition (Bi1.6Pbo.4Sr2 RExCa2-xCu3 0 y), the phases Bi(Pb)-2223 and Bi(Pb)-2212 (mixed phases) co-exist in the doped samples. The crystallographic structures underwent a transition from tetragonal (a=b≠c) to orthorhombic (a≠b≠c) as doping concentration of Eu and Yb were increased due to contraction of c-lattice. Eu and Yb were detected in the grains of Eu-doped and Yb-doped Bi(Pb)-2223 superconductor implying that both atoms were successfully doped into the crystal structure of low density Bi(Pb)-2223.